Parents’ Knowledge toward Pediatric Immunization and its Relation with their Compliance at Primary Health Care Centers in Karbala City (Indian Journal of Forensic Medicine & Toxicology, 2021)
Parents are their children’s primary health decision makers, their knowledge towards immunization ingeneral have a significant effect on the immunization status of their children. A descriptive (cross-sectionalstudy) was conducted to assess parents’ knowledge toward immunization and its relation with pediatricimmunization compliance at primary health care centers in Karbala city, IraqA non-probability (convenience) sample of 292 parents selected from (5) primary health care centers.These centers distributed throughout (2) primary health care sectors selected randomly as (20%) from eachsectors. The results of the present study indicated that the majority of studied parents had moderate levelof knowledge, which was a significant associated with their age of fathers, level of education of fatherand mothers, occupational status of mothers, family type, , more than sixty present of studied parentshave children partially immunized. In addition, the present study revealed that parents’ knowledge nothad a significant influence on child’s immunization status. So, this study recommendedit is necessary toraise parents awareness of the importance of immunization by implementing educational programs and bytraditional and social media with emphasis on time, side effects, contraindication, and disease preventableby immunization and promote periodically assessment for immunization coverage.
Keywords: Parents, Knowledge, Immunization, Compliance.